If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + -6(2b + -5) = 0 Reorder the terms: 35 + -6(-5 + 2b) = 0 35 + (-5 * -6 + 2b * -6) = 0 35 + (30 + -12b) = 0 Combine like terms: 35 + 30 = 65 65 + -12b = 0 Solving 65 + -12b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + -12b = 0 + -65 Combine like terms: 65 + -65 = 0 0 + -12b = 0 + -65 -12b = 0 + -65 Combine like terms: 0 + -65 = -65 -12b = -65 Divide each side by '-12'. b = 5.416666667 Simplifying b = 5.416666667
| 12n-6/5 | | 7z+21=8z | | 9y+36=-20y-4 | | 4x^2-1x+9=0 | | W×3/4=w-2/2 | | b/71.9 | | 7/6x=65 | | -3(4c-5)= | | X-(1-3X^2)=2X-(-X-3) | | 1/4x-1/8=4 | | 7g-6=-12+8g | | 21m^2-41m+21=0 | | 45.81=9n | | 17-7z-8=-16-12z | | 2ab+4= | | x-90=6-2 | | -13+18b=17b | | 64/121•-57/88-8/11 | | f/6=2.5 | | X-(1-3X)=2-(-X-3) | | 28-28-4(x-5)=-4 | | y=9.75(3.5)+20.75 | | 30y+4=-2 | | -5k+6k-18=12-k | | 3x-90=6-2 | | k/3-2k=4=10 | | 12+2t-0.25t^2= | | 11p-10=6+12p | | 2x+5=7x+3 | | 13b-8(b-2)=46 | | 5c=7c+10 | | y=1.3(-4)+12 |